MANAJEMEN SISTEM KEUANGAN DESA DALAM PENGELOLAAN ALOKASI DANA DESA DI DESA KONDANG JAYA KABUPATEN KARAWANG - Ahmad Maqribi Meidina; Cucu Sugiarti; Evi Priyanti (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
This study aims to determine and describe the implementation of managementfunctions in the apparatus for managing village fund allocations in Kondang JayaVillage. This study uses a qualitative approach with a descriptive type. There weretwo informants in this study, namely the village head and the head of financialaffairs. Data collection techniques used are observation, interviews, anddocumentation studies. The data analysis technique used is the inductive technique.The results showed that the management of the village fund allocation in KondangJaya Village was in accordance with the existing rules. From the village fundallocation planning process, ADD management, and reporting, all have beencarried out in accordance with applicable procedures. So, later, it is hoped that thisADD fund can create equitable and beneficial development for the Kondang Jayavillage community.